2000
DOI: 10.1177/002194360003700402
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Communication Direction on Job Performance and Satisfaction: A Moderated Regression Analysis

Abstract: High levels of job performance and job satisfaction occur when congruence of individual needs (growth need strength) and job characteristics (job scope) exists. Downward communication received some statistical support as both moderator and predictor of job performance and job satisfaction in low individual-job congruence situations. Upward and lateral communication had some support as predictors but lacked support as moderators of job performance and job satisfaction in high individual-job congruence situation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 40 publications
6
67
0
2
Order By: Relevance
“…Other variables (such as interpersonal relations, downward communication, security, remuneration and a need for independence) have also been shown to moderate the relationship of individual-job congruence with performance and/or satisfaction (Goris, Vaught & Pettit, 2000;Clayton, 1981;Oldham, Hackman & Pearce, 1976).…”
Section: Purpose Of the Jcmmentioning
confidence: 99%
“…Other variables (such as interpersonal relations, downward communication, security, remuneration and a need for independence) have also been shown to moderate the relationship of individual-job congruence with performance and/or satisfaction (Goris, Vaught & Pettit, 2000;Clayton, 1981;Oldham, Hackman & Pearce, 1976).…”
Section: Purpose Of the Jcmmentioning
confidence: 99%
“…There's a meaningful relation between dimension of organizational communication and staff commitment. Many authors showed a similar results but no such a result observed in Maleki et al study (Brunetto & Farr-Wharton, 2004;Goris, Vaught, & Pettit, 2000). Through proper communication, the organization goals are announced to staffs that the way of this communication and notifying it affect the organizational commitment.…”
Section: Discussionmentioning
confidence: 83%
“…The effect of organizational communication on the levels of commitment between employees has attracted the attention of some researchers (Goris et al, 2000;Pettit et al, 1997;Stuart, 1999). As Stuart (1999) argued, communication construction can affect empowerment of employees, which in turn affects organizational commitment.…”
Section: Communication Satisfaction and Organizational Commitmentmentioning
confidence: 99%